HUBUNGAN TINGKAT STRES TERHADAP KUALITAS TIDUR PADA PASIEN DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS GANG SEHAT PONTIANAK SELATAN - Syifa Yuni Zayajarda Anwar, Uray Nurul; Anggraini, Rara; Putri, Triyana Harlia (ProNers, 2021)
Diabetes mellitus is a hyperglycemia disease due to cell insensitivity to insulin, which can increase glucose levels in the blood and an increase in the hormone adrenaline which converts glycogen reserves into glucose, causing a person to stay awake at night, thus disrupting sleep quality. Method : This study used quantitative research with cross sectional design. The sampling technique used was purposive sampling method with a sample of 80 outpatients. The research was conducted by filling out the Perceived Stress Scale Pittsburgh Sleep Quality Index questionnaire. Research data using the Chi-square statistical test. Results : In this study patients diabetes mellitus of the were aged 56-65 years (50%), gender of female was 47 people (58.7%), last education was 22 people (27.5%), IRT employment status was 39 people (48.7%), experienced stress levels, and disturbed sleep quality. Bivariate analysis with Chi-square test obtained a value p = 0.025 ( p 0.05 ). Conclusion : There is correlation of stress levels to sleep quality in diabetes mellitus patients in the working area of Gang Sehat community health center subdistrict South Pontianak. Keywords: diabetes mellitus, stress level, sleep quality